(untitled) (Tempo e Argumento, 2013)
This article examines aspects of the Brasiliana collection, when it was under the direction of Americo Jacobina Lacombe, and História Geral da Civilização Brasileira(HGCB), which at the time was coordinated by Sérgio Buarque de Holanda. The study covers the period between the years of 1956 and 1972 and includes bibliographic and documentary sources, particularly from personal files of the mentioned authors when referring to the publishing ventures they organized. Its primary purpose is to reflect on the institutionalization and academic specialization of the History area in Brazil, shown through the process of organization of such collections.